Interface engineering of bi-layer semiconductor SrCoSnO3-δ-CeO2-δ heterojunction electrolyte for boosting the electrochemical performance of low-temperature ceramic fuel cell. (1st October 2021) - Shah, M.A.K. Yousaf; Tayyab, Zuhra; Rauf, Sajid; Yousaf, Muhammad; Mushtaq, Naveed; Imran, Muhammad Ali; Lund, Peter D.; Asghar, Muhammad Imran; Zhu, Bin
Abstract: A comparative study is performed to investigate the electrochemical performance of the low-temperature ceramic fuel cells (CFCs) utilizing two different novel electrolytes. First, a perovskite semiconductor SrCo0.3 Sn0.7 O3-δ was used as an electrolyte in CFCs due to its modest ionic conductivity (0.1 S/cm) and demonstrated an acceptable power density of 360 mW/cm 2 at 520 °C. The performance of the cell was primarily limited due to the moderate ionic transport in the electrolyte. In order to improve the ionic conductivity, a new strategy of using a novel bi-layer electrolyte concept consist of SrCo0.3 Sn0.7 O3-δ and CeO2-δ in CFCs. These bi-layers of two electrolytes have successfully established heterojunction which considerably improved the ionic conductivity (0.2 S/cm) and enhance the open-circuit voltage of the cell from 0.98 V to 1.001 V. Moreover, the CFCs utilizing bi-layer electrolyte have produced a remarkable power density of 672 mW/cm 2 at 520 °C. This enhancement of ionic conduction, power density and blockage of electron conduction in the bi-layer electrolyte was studied via band alignment mechanism based on proposed p-n heterojunction. Our work presents a promising methodology for developing advanced low-temperature CFC electrolytes. Graphical abstract: Image 1 Highlights: SrCoSnO3-δ -CeO2-δ semiconductor materials have been applied as a bi-layer electrolyte for CFC. The bi-layer electrolyte has a remarkable ionic conductivity of 0.2 S/cm. The fuel cell device produced 672 mW/cm 2 at 520 °C. Bi-layer electrolyte was studied via band alignment mechanism based on proposed p-n heterojunction.